The Lack of Social Well-Being in Two Disadvantaged Hungarian Micro-Regions - Nóra Baranyai; Júlia Schuchmann (DETUROPE)
The main objective of this paper is to reveal the crucial economic and social factors determining the lack of social well-being in two disadvantaged micro-regions of different geographical locations in Hungary, and to summarize the similarities and differences between them. The study also compares the two analysed cases in terms of subjective well-being, as well as indicators of micro-regions and urban areas located in the same county in order to demonstrate the inter- and intraregional differences. According to the hypothesis, basically the east-west determined spatial inequalities of objective social well-being emerge also in connection with subjective well-being issues. The results are based on an empirical research using qualitative and quantitative methods conducted in 2014.